Characterization and evaluation of mountain sweet thorn (Flacourtia montana J. Grah) collections - P C Tripathi (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2021)
Mountain sweet thorn (Flacourtia montana J. Grah) is an indigenous underutilized fruit of the Western Ghats and other regions of peninsular India. It is a close relative of Governor’s plum. It is a bushy shrub or small tree with spiny trunks and branches which may grow up to 2.5 m in height. The fruits are bright dark red 1-2 cm in diameter, sweet edible, and have the potential for processing into jams and jellies. The presence of thorn is one of the major hurdles for the commercialization of this crop. Thus, seeds of the thorny plants of the Mountain sweet thorn were collected from different locations, and seedlings were planted to identify the suitable line. The plant height ranged from 425 cm (accession 0208) to 710 cm (accession​ ​0202). The plant girth ranged from 34.5 cm to 82 cm. The growth data revealed that all​ ​the accessions are vigorous, fast-growing, and have various levels of thorniness. All the​ ​accessions were found to be spreading type. Significant variability was recorded for leaf​ ​characteristics among the accessions studied. Three major clusters were observed in​ ​cluster analysis for morphological and fruiting characters consisting of 1, 8, and 9 accessions,​ ​respectively. The number of fruits ranged from 0 to 4008. The highest yield (9.46 kg/plant)​ ​was obtained in accession - 0106 followed by accession- 0201 (7.83 kg). The average​ ​fruit weight ranged from 1.51 g to 3.94 g. The highest fruit weight (3.94g) was also recorded​ ​in 0106 followed by 2.84 (0102). The total soluble solids ranged from 10 0 Brix to 15.1 0​ ​Brix. Overall, accession 0201 was found better than others with respect to yield, regular​ ​bearing, and less thorniness.